2016
DOI: 10.3390/toxins8110336
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of In-Solution Biorecognition Properties of Aptamers against Ochratoxin A

Abstract: Ochratoxin A (OTA) is a mycotoxin produced as a secondary metabolite by several species of Aspergillus and Penicillium and frequently found as a natural contaminant in a wide range of food commodities. Novel and robust biorecognition agents for detecting this molecule are required. Aptamers are artificial nucleic acid ligands able to bind with high affinity and specificity to a given target molecule. In the last few years, three separate research groups have selected aptamers for ochratoxin A. While each of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 33 publications
5
33
0
Order By: Relevance
“…50 Similarly, studying the binding of these aptamers to OTA through various insolution binding parameter, we are able to recommend which sequences are best suited for these solution-based assays and applications. 51 Interestingly, 1.12.2, A08, A08m H8…”
Section: Assay Dependent Differences In Small Molecule Aptamer Evaluamentioning
confidence: 97%
See 1 more Smart Citation
“…50 Similarly, studying the binding of these aptamers to OTA through various insolution binding parameter, we are able to recommend which sequences are best suited for these solution-based assays and applications. 51 Interestingly, 1.12.2, A08, A08m H8…”
Section: Assay Dependent Differences In Small Molecule Aptamer Evaluamentioning
confidence: 97%
“…Similarly, the affinity of the aptamer for its target can vary depending on the binding conditions. 50,51 In a collaborative study, our research group reported that not all aptamers with affinity for a small molecule target (OTA) were capable of detecting the target through the AuNP assay. Optimization of the sensor parameters is often required when applying the sensor platform to a new aptamer sequence and target molecule.…”
Section: Current Challenges With Aptamer-based Gold Nanoparticle Assaysmentioning
confidence: 99%
“…One of the potential limitations for the widespread use of aptamers is the lack of standardized characterization methods. 65 No single method is can perfectly describe the binding capabilities of an aptamer. Moreover, careful consideration must be taken for sample conditions in which aptamers are characterized when comparing Kds.…”
Section: Measuring Aptamer Affinitymentioning
confidence: 99%
“…Mckeague et al reported an analytical comparison process that highlighted the inconsistencies in the many conventional aptamer affinity assays that are frequently used for characterization. 65 It has been suggested that strategies that allow the binding characterization of many aptamers in a parallel manner would help the advancement of low throughput characterization. 48 While MST is a suitable method for determining binding parameters of an aptamer that is free in solution.…”
Section: Chapter: Contributions To Knowledge and Future Studiesmentioning
confidence: 99%
See 1 more Smart Citation